From signals to sustenance: the role of biogenic amines in insect feeding behavior - Patil, Yogita P.; Joshi, Rakesh S. (Journal of Insect Behavior, 2025)
Insect feeding is a complex and finely-tuned behavior that notably impacts their physiological and metabolic processes. Chemical signals and cues, chemosensation, motor response, and physiological changes govern responses to food resources. The role of biogenic amines in regulating feeding is essential, as they significantly affect locomotory changes and nutrient assimilation. Octopamine, tyramine, dopamine, serotonin, and other biogenic amines are neuromodulators, neurotransmitters, and neurohormones. Octopamine and tyramine have contrasting effects on food-seeking and foraging behavior regulation. The interaction among biogenic amines and their respective receptors initiates diverse signaling pathways by modifying the concentrations of intracellular secondary messengers like Ca2+, AMP, and other molecules. These signal transductions regulate various physical and metabolic processes, directly influencing feeding behavior and digestive physiology. Furthermore, dopamine triggers a negative response, whereas serotonin plays a positive role in regulating feeding behavior. Biogenic amines underlie synchronized and interconnected molecular mechanisms, along with unique individual effects. It is fascinating to consider these interrelated activities and the impacts of bioamine on insect feeding behavior. In this review, we discuss the roles of insect biogenic amines and their cross-talk in insect feeding and foraging behavior.
Keywords: Biogenic amines; feeding behavior; octopamine; Signal transduction; tyramine